Structural, Optical, and Mechanical Properties of Polyvinylpyrrolidone/Graphene Oxide Microfibers for Optoelectrical Applications - Shahab Kharazmi (Nanochemistry Research)
Microfiber-shaped materials have recently gained attention as a highly promising type of energy storage devices due to their exceptional flexibility, high energy density, and long cycle life. In this study, polyvinylpyrrolidone (PVP) nanocomposite films containing graphene oxide (GO) in three different volume fractions of GO as filler (PVP/GO-F: 0.01, 0.03, and 0.05 wt.% GO) were prepared via a simple stretching method as a highly luminescent and flexible material. X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), Fourier-transform infrared spectroscopy (FTIR), and luminescence measurement techniques were used to examine the structural and optical properties of these fibers. Furthermore, int the XRD patterns of PVP/GO-F samples, a characteristic graphene oxide peak appeared at 6.85◦ and increased with adding GO concentration. As the GO volume fraction increased in the PVP/GO nanocomposite fibers, the violet-blue luminescence intensity under UV lamp and room temperature increased. According to mechanical properties investigation, with adding graphene, the Young’s modulus and tensile strength increased while the elongation decreased.  Furthermore, FE-SEM images showed that microfiber diameter was obtained about 2.2 μm. These nanocomposite fibers are promising for using optics, electricity, optoelectronics, and many other industrial applications such as optical sensor and wearable optoelectronic applications.